2003
DOI: 10.1016/s1059-1311(02)00267-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar volume and long-term use of phenytoin

Abstract: CA is frequently associated with long-term use of phenytoin. Although duration of epilepsy may have an influence in the CA, this is clearly less important than the time of exposure to phenytoin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(69 citation statements)
references
References 12 publications
1
66
0
2
Order By: Relevance
“…Both cerebellar atrophy and hyperostosis of skull can be seen after long term phenytoin use. 1,2 Phenytoin is known to cause diffuse atrophy of purkinje cells of the cerebellum both clinically and experimentally. Along with the drug's action, cerebellar atrophy post phenytoin therapy in epileptic patients is also attributed to seizure mediated cell loss secondary to ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both cerebellar atrophy and hyperostosis of skull can be seen after long term phenytoin use. 1,2 Phenytoin is known to cause diffuse atrophy of purkinje cells of the cerebellum both clinically and experimentally. Along with the drug's action, cerebellar atrophy post phenytoin therapy in epileptic patients is also attributed to seizure mediated cell loss secondary to ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…The size of sulci and foliae are used to assess the degree of cerebellar atrophy. 2 The common differential diagnoses of cerebellar atrophy include Alcoholic atrophy, Multi system atrophy (MSA) and Ataxia telangiectasia.…”
Section: 4mentioning
confidence: 99%
“…The main substances causing toxic ataxia are: lithium, phenytoin, amiodarone, toluene and some chemotherapy's (5-fluorouracil and cytosine arabinoside) [10][11][12][13][14] . There are also descriptions of ataxia induced by mercury or bismuth subsalicylate exposure 15,16 .…”
Section: Ataxia Related To Toxic Causesmentioning
confidence: 99%
“…Although few data exist about the risk of SUDEP in children, a recent study by our research group demonstrated that increased SUDEP occurrence appeared in children unresponsive to antiepileptic therapy, with no increase in risk observed in patients who remained seizure free 31 . An additional important issue is evidence that phenytoin can exert toxic effects on the cerebellum in patients with epilepsy 32 ; the toxicity is associated with ataxia, tremor, nystagmus and diplopia 32,33 . Furthermore, cerebellar atrophy can occur in phenytoin-exposed patients with epilepsy in the absence of generalised tonicclonic seizures or pre-existent brain damage 32,34,35 .…”
Section: Brain Regions and Sudepmentioning
confidence: 99%